Dilemma of duties: the conflicted role of juvenile defenders - Corbin, Anne M. (Perspectives on crime and justice, 2018)
"Author Anne M. Corbin examines the unique role of defense counsel in juvenile courts, demonstrating the commonplace presence of role conflict, even among defenders in jurisdictions that clearly define this role, and showing the nature, extent, and impact of that role conflict on juvenile justice system stakeholders, processes, and policy"--